Knowledge, Attitude and Practice on Guided Implant Surgery Among Undergraduate Dental Students - HARIKRISHNAN, RESHMA; GANAPATHY, DHANRAJ; R, SUBHASHREE. (The journal of contemporary issues in business and government, 2020)
Dental implant surgery is the procedure in which replaces both the missing tooth and root with a stable, metal post called an implant. There are many significant drawbacks to the dental procedure and they include time consuming and invasive, a longer duration of treatment, patient cooperation, expensive, need for precision and subsequent follow up visits. A guided implant surgery is when the dentist utilizes advanced machinery and imaging technology to aid in the manufacture and placement of the dental implant in a more efficient, precise and accurate manner. The aim of this study is to assess the knowledge of Undergraduate students in the field of implantology and to check their views regarding easier and more accurate placement of implants. A questionnaire based survey was done among 100 dental students. Probing questions regarding their knowledge of guided implant surgery were asked. The results were tabulated and analysed to get the result. It was seen that the majority of the students were aware of the advances in dental implantology. They understood the advantages of a guided implant surgery